'The opposite of a European democracy': the American real estate lobby, French and British social housing, and the making of the postwar American welfare state, 1945–1949. (2nd January 2017) - Zdencanovic, Ben
Abstract : This article takes a new approach to the question of postwar American welfare state 'exceptionalism' by arguing that scholars should look at ideas and discourses of American welfare exceptionalism in historical context as a social construct and a political project. By focusing on the National Association of Real Estate Boards' lobbying campaign against US public housing legislation in the late 1940s, I show that US business interests often used the example of Western European welfare state initiatives in order to not only decisively shaped specific pieces of social legislation, but to contest the very meaning of the postwar New Deal state.